Internalisasi Nilai-Nilai Agama Islam dalam Pembentukan Karakter Peserta Didik di Sekolah Dasar Negeri 116 Buton Kabupaten Buton - Marwan Kurniawan Rahim (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2024)
This research discusses the internalization of Islamic religious values ​​in the formation of students' character at 116 State Elementary Schools, Buton Regency. Aims to describe the internalization of Islamic religious values ​​in forming the character of students at SD Negeri 116 Buton and describe the factors that influence the internalization of Islamic religious values ​​in forming the character of students at SD Negeri 116 Buton. This research uses pedagogical research to determine the ability of educators to carry out the learning process, especially in terms of their pedagogical competencies. The implementation of learning starts from planning, implementing and evaluating learning outcomes and being able to understand students from all their characters, especially in increasing interest in learning and psychological research referred to in this research is research that is based on the objective conditions of the students being researched by considering the conditions faced by them. students, especially when learning takes place and the condition of educators when carrying out learning. The research results show that the implementation of the integration of PAI learning values ​​is carried out by teachers in the learning process through the preliminary, core and closing stages. The values ​​instilled are in accordance with the basic competencies that have been planned. The character value that often appears is religious character. The implementation of PAI integration education at SD Negeri 116 Buton attracted quite a lot of attention because all subject teachers were required to master Islamic Religious Education. The role of teachers is very dominant in the formation of the religious character of their students in the future. Behind the success of students there is always a competent teacher who provides great inspiration and motivation to them as a source of energy to always learn and move to catch up, achieve progress and achieve their goals. The main thing for a student is that by utilizing the infrastructure, students are able to accept the teacher's explanation and are more interested in following the lesson. In order to improve the quality of educational institutions in global competition in positive terms in education and to shape the character of students, continuous efforts are needed to achieve goals. Several obstacles, one of which is the lack of facilities and infrastructure so that they are unable to provide a conducive atmosphere for students, learning equipment that is still simple, toilet facilities are inadequate compared to the large number of students and so on. The conclusion of this research is that the internalization of the values ​​of Islamic religious education through learning from the preliminary stages, from the learning process to the end of learning, becomes an integral series, this can be implemented with adequate facilities and infrastructure even though there are still obstacles in its implementation.